Los sistemas de beneficiado del café costarricense: 1830-1914 - Naranjo Gutiérrez, Carlos (Revista de historia., 2007)
This article seeks to present a different point of view with regards to the traditional preeminence of wet coffee processing over other methods. The analysis is based on a qualitative database put together after the study of a wide variety of sources such as newspapers, census, protocols, court records, municipal records, books, etc. At the same time, it takes on a historical review of the introduction of foreign technology and the native innovation to develop a coffee bean of acceptable export quality. Likewise, the article stresses on the technical problems faced by the Costa Rican coffee industry.